Product and Vendor Development Programme in Encouraging Supply Chain Management: A Case Study - Wan Mahmood, Wan Hasrulnizzam; Ab Rahman, Mohd Nizam; Md Deros, Baba; Ismail, Ahmad Rasdan (2010)
This paper reviews the methods used by an automotive manufacturer in enhancing the Supply Chain Management (SCM) system through a setup termed as Product and Vendor Development Programme (PVD). PVD was developed to eliminate problems faced due to late delivery and poor quality of supplies and availability of supplies at the lowest possible costs. The paper explores the methodologies that have been employed by the PVD. Results overtime show that the PVD has improved the SCM system especially in the areas of quality and delivery services, other services and as well as cutting costs that manufacturers had to face due to problems that arose in the shortcomings of the supply services. The PVD has managed to promote the Localization Programme and has also been able to establish qualified vendors. Findings also establish that the PVD team is the key to the success for development of the PVD programme. The paper presents an original discussion about viewing PVD programme from a successful automotive manufacturer.